Особливості тензорезистивного ефекту аморфних металевих сплавів при різних типах деформації - Семенько, М.П.; Захаренко, М.І.; Макара, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The formulas for tensoresistance coefficients in the cases of uniaxial tension and compression, as well as of uniform compression, are obtained using the Faber–Ziman theory in the assumption that changes of the electric resistance R under external stress σ mainly arise due to changes of the structural factor. The estimations by the proposed relations are in good agreement with the experimental results for uniaxial tension and compression and with the reference data for uniform pressure.